Risiko Likuiditas pada Perbankan Konvensional dan Syariah di Indonesia - Faisusza Bani; Rizal Yaya (Jurnal Riset AKuntansi dan Bisnis, 2016)
This study compares risk liquidity at Islamic and conventional bank in Indonesia and analyses factors that affect it. Data used are quarterly report of islamic and conventional banks from March 2008- March 2014 where the samples were selected based on purposive sampling and analysed based on multiple regression analysis. The findings show that there is a significant difference between islamic and conventional banks on risk liquidity. This study also found that Capital Adequacy Ratio (CAR) and Return on Asset (ROA) have negatif effects while Net Interest Margin (NIM) has positive effects on risk liquidity of Islamic banks. No financial ratios were found had effect on risk liquity of conventional banks. In terms on company size, it was found that it has no effect on risk liquidity in both Islamic and conventional banks.